2018
DOI: 10.1186/s40781-018-0177-5
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the xanthosine response on gene expression of mammary epithelial cells using RNA-seq technology

Abstract: BackgroundXanthosine treatment has been previously reported to increase mammary stem cell population and milk production in cattle and goats. However, the underlying molecular mechanisms associated with the increase in stem cell population and milk production remain unclear.MethodsPrimiparous Beetal goats were assigned to the study. Five days post-partum, one mammary gland of each goat was infused with xanthosine (TRT) twice daily (2×) for 3 days consecutively, and the other gland served as a control (CON). Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
2
0
0
Order By: Relevance
“…We firstly observed an increasing xanthosine in the skin lesions of psoriasis patients. Previous studies revealed that xanthosine can promote cell proliferation and differentiation and prevent excessive recruitment of white blood cells to inflammatory sites 31,32 . Similarly, increased inosine was found in psoriatic lesions and positive correlated with PASI score in this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We firstly observed an increasing xanthosine in the skin lesions of psoriasis patients. Previous studies revealed that xanthosine can promote cell proliferation and differentiation and prevent excessive recruitment of white blood cells to inflammatory sites 31,32 . Similarly, increased inosine was found in psoriatic lesions and positive correlated with PASI score in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies revealed that xanthosine can promote cell proliferation and differentiation and prevent excessive recruitment of white blood cells to inflammatory sites. 31,32 Similarly, increased inosine was found in psoriatic lesions and positive correlated with PASI score in this study. Koizumi et al demonstrated that increased activity of adenosine deaminase was F I G U R E 6 Correlation between seven biomarkers and the PASI scores (all p < 0.05).…”
Section: Nucleotide Metabolismsupporting
confidence: 79%